Cardiac blood cyst with concomitant papillary fibroelastoma. Issue 2 (February 2021) - Yada, Masashi; Nishina, Takeshi; Sato, Shun; Ueda, Yuichi; Yamanaka, Kazuo
Abstract: Cardiac blood cyst in adults is a rare benign tumor. Cardiac blood cyst concomitant with another type of cardiac tumor has never been reported. We report a case of a 77-year-old woman with cardiac blood cyst and papillary fibroelastoma. We performed resection of both tumors. An encapsulated mass (15 mm in diameter) with short stalks was identified in the right atrium, and a soft 1-cm mass was found adhering to a large part of the aortic valve noncoronary cusp without stalks. Postoperative course was uneventful. <Learning objective: Blood cyst of the heart is a rare benign tumor. Cardiac blood cyst concomitant with another type of cardiac tumor has never been reported. We report a case of a 77-year-old woman with cardiac blood cyst and papillary fibroelastoma. We performed resection of both tumors. We think surgical resection in asymptomatic patients is a feasible option, taking the risk of embolization into consideration.>